2020
DOI: 10.1021/acs.jpcc.0c01039
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Interaction Promotes Flash Energy Transport at MXene-Solvent Interface

Abstract: There are emerging applications for photothermal conversion utilizing MXene, but the mechanism under these applications related interfacial energy migration from MXene to the attached surface layer is still unknown. Here, the femtosecond pump–probe spectroscopy is employed to elucidate the ultrafast electronic energy dissipation pathways of MXene (Ti3C2T x ) under plasmonic excitation. The experimental results suggest that in water, nearly 80% energy in MXene gained from the photoexcitation quickly dissipates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…A very recent ultrafast study reported the dynamic processes of Ti 3 C 2 T x on different interfacial conditions, including aqueous solution, ethanol solution, and polymer mixture. [143] As shown in Figure 8d, the thermal dissipation pathways could be divided into a hydrogen bond dominated fast channel and a lattice motion mediated slow channel. Compared with MXene thermal dynamics in different solvents, the effective hydrogen bonding between Ti 3 C 2 T x and water molecules significantly promote fast interfacial energy migration, showing the prominent interfacial thermal conductance of Ti 3 C 2 T x -water larger than 100 MW K −1 m −2 .…”
Section: Ultrafast Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A very recent ultrafast study reported the dynamic processes of Ti 3 C 2 T x on different interfacial conditions, including aqueous solution, ethanol solution, and polymer mixture. [143] As shown in Figure 8d, the thermal dissipation pathways could be divided into a hydrogen bond dominated fast channel and a lattice motion mediated slow channel. Compared with MXene thermal dynamics in different solvents, the effective hydrogen bonding between Ti 3 C 2 T x and water molecules significantly promote fast interfacial energy migration, showing the prominent interfacial thermal conductance of Ti 3 C 2 T x -water larger than 100 MW K −1 m −2 .…”
Section: Ultrafast Dynamicsmentioning
confidence: 99%
“…c,d) Reproduced with permission. [143] Copyright 2020, American Chemical Society. e) Schematic for MXene-surfactant interface energy migration process.…”
Section: Ultrafast Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen bonding (H-bonding) between water and host materials has proven to be important for the structure and function of the latter. [1][2][3] Strong H-bonds can lead to the formation of extended networks that modulate fundamental processes, including hydration processes, 4 chemical synthesis and reactions, 5,6 heat dissipation, 7,8 and macroscopic structural formations. 7,[9][10][11] Under confinement, H-bonded networks are disrupted due to physical constraints and host-water interactions.…”
Section: Introductionmentioning
confidence: 99%
“…2b and Fig. S11a) could represent the MXene flakes' thermal energy decay [44]. The fitting results showed that proportion of the fast part of Ti 3 C 2 and S. aureus mixture is 9% less than that of Ti 3 C 2 in water, while the proportion of the slow part of Ti 3 C 2 and S. aureus mixture is 9% more than that of Ti 3 C 2 in water, indicating that the proportion of the fast part decreased, while the proportion of the slow part increased after mixing with S. aureus.…”
Section: Antibacterial Mechanisms Of Mxene With Lightmentioning
confidence: 99%